Mouse model of ulcerative colitis using trinitrobenzene sulfonic acid - Irfan Ahmad Rather; Vivek K. Bajpai; Nam Gyeong-Jun (Bangladesh Pharmacological Society, 2015)
Animal model of intestinal inflammation is of paramount significance that aids in discerning the pathologies underlying ulcerative colitis and Crohns disease, the two clinical presentations of inflammatory bowel disease. The 2,4,6-trinitrobenzene sulfonic acid (TNBS) colitis model represents one such intestinal inflammation-prototype that is generated in susceptible strains of mice through intra-rectal instillation of compound TNBS. In this paper, we demonstrate the experimental induction of TNBS-mediated colitis in a susceptible strain of ICR mice. This can be done by the following steps: a) acclimation, b) induction and c) observation. TNBS-mouse model provides the information in shortest possible time and simultaneously represents a cost effective and highly reproducible model method of studying the pathogenesis of inflammatory bowel disease. Video Clips of Methodology: Acclimation and induction of TNBS:   4 min 31 sec   Full Screen   Alternate Observation and drug administration:   1 min 31 sec   Full Screen   Alternate